The Influence of Price, Promotion and Trust on Shopeefood Purchase Decisions (Yogyakarta City Consumer Study) - Arief Rizky Pradana; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This research aims to find out if there is an influence on price, promotion, and trust on Shopeefood purchasing decisions. The population used in this study was Shopeefood consumers in Yogyakarta City. The study used questionnaires using Google Form as a research tool. This research method uses non-probability sampling techniques with purposive sampling methods. The sample was used by 100 respondents. The data is obtained from questionnaires which are then processed and analyzed using multiple regression test analysis with model accuracy (classical assumption test), hypothesis testing using determination coefficient test (R2), partial test (t test), and simultaneous test (F test) through SPSS 24 program. The results of this study showed that price variables positively influence purchasing decisions, promotions positively influence purchasing decisions, confidence positively influences purchasing decisions, simultaneous promotions, prices and beliefs have a positive and significant effect on purchasing decisions